PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP FINANCIAL DISTRESS - Irwanto, Affan (Jurnal Akuntansi AKUNESA, 2013)
Financial distress is bad condition for the companies. It can show from financial report companies had loss profit than before. The purpose of the research is to examine the influence of institutional ownership on financial distress in listing companies at BEI. The study uses analysis linier regression. The sample used of 33 companies from 54 companies that select random sampling in 2012. The result of the study showed that institutional ownership not significant effect on the financial distress. Keyword: Institutional Ownership, Financial Distress, Loss Profit.